Evaluation of the Larvicidal Activity Of The Root Extracts of Allamanda Cathartica L (Apocynaceae) On Aedes Aegypti Larvae - Lambert, Okwubie; Umunakwe, Onu (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Aedes aegypti is a species of mosquito that transmits yellow fever, zika virus fever, dengue fever and chikungunya diseases. Allamanda cathartica L is an evergreen tropical plant that is grown as a climbing vine or pruned as a shrub, belonging to the family Apocynaceae. The aim of this research is to evaluate the larvicidal activity of Allamanda cathartica root on Aedes aegypti larva. The acetone and methanol extracts were obtained by exhaustive soxhlet extraction, while the aqueous extract was obtained through maceration. A stock solution of 10mg/ml was prepared for each extract from which six different concentrations (0.5mg/ml, 1.0mg/ml, 2.0mg/ml, 3.0mg/ml, 4.0mg/ml and 5mg/ml in 100ml) were made and used for the test in accordance with World Health Organization (WHO) guideline. A control was also prepared for each extract by adding 1ml of the solvent to 100ml of water. A total of 25 larvae were used for each of the concentration and mortality was recorded at 24, 48 and 72 hours. The three extracts showed larvicidal activity against Aedes aegypti larva with acetone extract having the highest activity followed by methanol and aqueous extract respectively. At 72 hours, the LC50 of acetone, methanol and aqueous extracts were 0.61mg/ml, 2.98mg/ml and 6.52mg/ml respectively. The result shows that acetone extract of the root of Allamanda cathartica could be a veritable source of Larvicides.